Aortic Valve Plasty during Correction of Combined Mitral-Aortic Valve Diseases - Bolshak, O.; Boukarim, V.; Vitovskiy, R.; Bakhovska, Yu.; Popov, V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The aim. To study the experience of valve-preserving operations on the aortic valve combined with plasty of the left atrium in patients with atriomegaly (the first clinical experience). Materials and methods. The study included 1890 patients with combined mitral-aortic valve diseases (CMAVD) who were undergoing surgical treatment at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine in the period from 01/01/2006 to 01/01/2020. Of these, 156 (8.3%) underwent reconstructive intervention on the aortic valve during mitral valve replacement (MVR). Valve sparing procedures performed: - aortic valvotomy (93 patients); - aortic valvotomy + debridgment (30 patients); - aortic valvotomy + leaflet plication (4 patients); - removal of vegetation from the aortic valve (7 patients); - applying a patch of autopericardium on a leaflet (7 patients); - carpentier aortic valve annuloplication (2 patients); - aortic valve debridgment (12 patients); - aortic valve decalcification + Morrow operation (1 patient). All operations were performed under conditions of cardiopulmonary bypass (CPB) and moderate hypothermia (28-32 °C). Myocardial protection was carried out mainly by means of ante-retrograde pharmaco-cold cardioplegia with Custodiol solution in combination with external cooling of the heart. The time of aortic clamping was 82.4 ± 12.1 minutes, and the time of CPB was 117.5 ± 21.5 minutes. In 689 (78.4%) operated patients, blood loss was within 450 ml. In 29 (18.6%) patients, donor blood components were not used at the hospital stage. Conclusions. On the basis of the clinical experience gained, it seems appropriate to recommend reconstructive interventions on aortic valve with moderate changes in it in order to avoid traumatic two-valve prosthetics in the correction of combined mitral-aortic defects and to improve the survival rates and stability of good results.